School-based intervention to prevent overweight and disordered eating in secondary school Malaysian adolescents: a study protocol - Sharif Ishak, Sharifah Intan Zainun; Chin, Yit Siew; Mohd Taib, Mohd Nasir; Mohd Shariff, Zalilah (BioMed Central, 2016)
Background: Obesity, eating disorders and unhealthy weight-loss practices have been associated with diminished growth in adolescents worldwide. Interventions that address relevant behavioural dimensions have been lacking in Malaysia. This paper describes the protocol of an integrated health education intervention namely 'Eat Right, Be Positive About Your Body and Live Actively' (EPaL), a primary prevention which aimed to promote healthy lifestyle in preventing overweight and disordered eating among secondary school adolescents aged 13-14 years old. Methods/design: Following quasi-experimental design, the intervention is conducted in two secondary schools located in the district of Hulu Langat, Selangor, Malaysia. Adolescents aged 13-14 years will be included in the study. A peer-education strategy is adopted to convey knowledge and teach skills relevant to achieving a healthy lifestyle. The intervention mainly promoted: healthy eating, positive body image and active lifestyle. The following parameters will be assessed: body weight, disordered eating status, stages of change (for healthy diet, breakfast, food portion size, screen viewing and physical activity), body image, health-related quality of life, self-esteem, eating and physical activity behaviours; and knowledge, attitude and practice towards a healthy lifestyle. Assessment will be conducted at three time points: baseline, post-intervention and 3-month follow-up. Discussion: It is hypothesized that EPaL intervention will contribute in preventing overweight and disordered eating by giving the positive effects on body weight status, healthy lifestyle behaviour, as well as health-related quality of life of peer educators and participants. It may serve as a model for similar future interventions designed for the Malaysian community, specifically adolescents.